Blockages in the Romanian farmers performance - Davidovici, Ioan; Davidovici Alexandru, Sava; Kruzslicika, Mihaela (Economics of Agriculture, 2010)
The main factors that obstruct the best use of farmers productive potential are investigated and on this basis certain possibilities to surmount the present situation are highlighted.